“Jugando” a divulgar la física con juguetes - Varela Nieto, Mª.P.; Martínez Montalbán, J.L. (Revista Eureka sobre Enseñanza y Divulgación de las Ciencias, 2017)
En este artículo se presenta una propuesta para enseñar y divulgar Física utilizando juguetes. Se describe detalladamente la intervención de profesores y estudiantes “profesores” en las Ferias Madrid por la Ciencia y los programas de divulgación del Museo Nacional de Ciencia y Tecnología. Palabras clave: enseñanza de la física, juguetes, divulgación científica. "Playing" to divulge Physics with toys This article presents a proposal to teach and disseminate Physics using toys. It describes in detail the intervention of teachers and students "teachers" at the Madrid Science Fair and the programs of dissemination of the National Museum of Science and Technology. Key words: teaching of Physics, toys, scientific dissemination.